Chemical Constituents from the Leaves of Annona reticulata and Their Inhibitory Effects on NO Production - Ngo Xuan Luong (Molecules, 2013)
In the present study, the chemical investigation of the leaves of Annona reticulata has resulted in the identification of nine compounds, including annonaretin A, (1), a new triterpenoid. The purified compounds were subjected to the examination of their effects on NO inhibition in LPS-activated mouse peritoneal macrophages and most of them exhibited significant NO inhibition, with IC50 values in the range of 48.6 ± 1.2 and 99.8 ± 0.4 μM.